Hubungan Pengetahuan Swamedikasi dengan Perilaku Penggunaan Suplemen Vitamin C Masyarakat Kota Denpasar - Pungasti, Ni Kadek Ferdina (Bali International University, 2021)
ABSTRACTTHE RELATIONSHIP BETWEEN SELF-MEDICATION KNOWLEDGE AND THE BEHAVIOR OF USING VITAMIN C SUPPLEMENTS IN DENPASAR CITYNi Kadek Ferdina Pungasti1, Putu Eka Arimbawa2, I Made Bakta3Clinical Pharmacy Study Program, Faculty of Health Sciences, Bali International University. Email: ferdina.pungasti07@gmail.comBackground: Self-medication is one efforts made to overcome the symptoms of the disease before seeking help from health workers. In terms of disease prevention, one of the drugs that can be used through self-medication is vitamin C supplementation. Objective: This study aims to determine the relationship between knowledge of selfmedication and the behavior of usings vitamin C supplements in the people of Denpasar City. Methods: This study is an analytic observational study with a crosssectional design approach. 100 respondents in this study were determined by inclusion criteria: willing to fill out a questionnaire, 18-25 years, able to read and write, had self-medication and had used vitamin C supplements. Purposive sampling technique was carried out using a questionnaire in the Denpasar City area from February 2022 to April 2022. Data analysis used in this study is the Spearman Rank Test. Results: 64% of respondents have a good level of self-medication knowledge and 58% of respondents have positive behavior related to the use of vitamin C supplements. Spearman test results obtained p-value 0.029, correlation coefficient 0.219. Conclusion: There is a significant relationship between knowledge of self-medication and the behavior of using vitamin C supplements in the people of Denpasar City with a weak correlation level.